SIMULATION OF INTERNAL AUDIT WITHIN THE DEPARTMENT OF HUMAN RESOURCES IN AN ECONOMIC ENTITY FROM THE PUBLIC SECTOR - BOGDAN RĂVAŞ (Annals of the University of Petrosani: Economics, 2015)
The theoretical research in the fields - internal audit and human resources aims to explain why successful companies have failed to implement effective strategies and policies and effective internal audit and human resources through the application of appropriate models for assessment and analysis activities and specific processes and identifying good practices. The scientific approach was based on the analysis of the operational performance of processes and activities of internal audit and human resources and the size analysis behaviours of the organization as a component of the human resources strategy, which together with marketing strategy and production, are part of a strategic plan of the company.